The Stepwise Smartphone Application Co-creation of innovative agricultural extension support tools - International Institute of Tropical Agriculture (2019)
To support the roll-out of the Stepwise approach a Smartphone application was developed as a tool for use by impact partner extension workers. IITA partnered with Mango Tree, an educational, communication and design company based in Uganda (https://mangotreeuganda.org/) combining research and technical knowledge with creative expertise to develop an appealing and innovative application. IITA impact partners, Hanns R. Neumann Stiftung and Olam contributed insight on information delivery and field-based data collection needs to maximize the usefulness of the application to the private sector.